UPAYA MENINGKATKAN HASIL BELAJAR IPS DENGAN METODE PREDICTION GUIDE - Resi Siagian (Prodi Pendidikan Guru Sekolah Dasar, 2022)
This study aims to find out how the activity steps in the implementation of the Prediction Guide learning method are able to increase social studies learning outcomes in Class IX-12 SMP Negeri 2 Padangsidimpuan. This research is a descriptive qualitative classroom action research (CAR), which was conducted collaboratively between researchers and teachers involving 27 students. As a collaborative research, the researcher acts as a participant implementing the action, and a fellow teacher is invited as a collaborator who acts as an observer. Data was collected through observation and analysis of learning outcomes, the findings were then analyzed descriptively qualitatively according to the relevant theories. This study further proves that the implementation of the Prediction Guide learning model is able to improve social studies learning outcomes in Class IX-12 at SMP Negeri 2 Padangsidimpuan. This can be seen from the increased ability of students to understand the subject matter, increased participation and learning activities, and increased achievement of test scores. However, the implementation of learning activities with this method requires the maximum ability to guide and direct the teacher. This research still suggests other relevant research to obtain much more satisfactory results.